(untitled) (LACCEI, 2024)
At present, the agricultural sector has become dependent on the use of synthetic fertilizers, with the aim of supplying nutrients and promoting the productivity of various crops. However, its prolonged application has been shown to be detrimental to the soil and the microbiome. Nanotechnology is presented as an efficient and ecological alternative as nanonutrients, which allows the slow and sustained release of nutrients. This research evaluates the influence of the concentration of iron oxide nanoparticles (FeO NP) in the germination process of Chenopodium quinoa. The nanoparticles were obtained by a sustainable method, achieving high monodispersity and spherical geometry. The application as nanofertilizers showed a significant effect compared to the control sample, which allows us to determine that the size of the nanomaterial promotes the improvement of nutrient absorption mechanisms, in addition to contributing at an elemental level to root development and germination rate.